Nilai Karakter Demokrasi dan Peduli Sosial pada Komik Digital Webtoon ‘Study Group’ untuk Generasi Alpha: Penelitian - Rahma Aditya Kusumawardani; Hidar Amaruddin (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This research aims to describe and categorize the character education values of democratic values and social care in the Webtoon digital comic entitled Study Group for the alpha generation. Data sources in this study, using primary data sources of data collected directly from the original source, and secondary data obtained from indirect sources or those already collected by other parties. as for the data collection technique in this study is document analysis, namely data in the form of various forms of documents and works of art referred to as content analysis (content analysis for descriptive research or analysis of meaning for inferential research). The results showed that overall, this Webtoon Study Group succeeded in conveying democratic character values and social care that are important in the character building of Alpha Generation children who like digital things.